Sonographic Optic Nerve Sheath Diameter: A Simple and Rapid Tool to Assess the Neurologic Prognosis After Cardiac Arrest. Issue 6 (19th April 2015) - Ueda, Takeshi; Ishida, Eri; Kojima, Yusuke; Yoshikawa, Satoshi; Yonemoto, Hitoshi
ABSTRACT BACKGROUND AND PURPOSE The early prediction of hypoxic encephalopathy after cardiac arrest is challenging. Measurement of the optic nerve sheath diameter (ONSD) by using sonography is a straightforward, noninvasive technique to detect an increased intracranial pressure, which can even be conducted at the bedside. However, it remains unknown whether or not sonographic ONSD measurement is valuable as a prognostic indicator of hypoxic encephalopathy. METHODS Seventeen patients after cardiac arrest were retrospectively enrolled in this study. ONSD measurements 3 mm behind the papilla were recorded. A Glasgow Outcome Scale score of 4 or above was considered to indicate a favorable prognosis. RESULTS The mean ONSD associated with a favorable prognosis was 5.0 mm (4.4‐6.1 mm). The ONSD associated with a poor prognosis was 6.1 mm (5.4‐7.2 mm). ONSD less than or equal to 5.4 mm was an indicator of a favorable prognosis, with a sensitivity of 83%, specificity of 73%, positive likelihood ratio of 3.1, and negative likelihood ratio of .23. CONCLUSIONS Sonographic ONSD measurement is a simple, rapid technique to assess the neurological prognosis after cardiac arrest.